Probing Clostridium difficile Infection in Complex Human Gut Cellular Models - Anonye, Blessing O.; Hassall, Jack; Patient, Jamie; Detamornrat, Usanee; Aladdad, Afnan M.; Schüller, Stephanie; Rose, Felicity R. A. J.; Unnikrishnan, Meera (Frontiers in Microbiology, 2019)
Interactions of anaerobic gut bacteria, such as Clostridium difficile, with the intestinal mucosa have been poorly studied due to challenges in culturing anaerobes with the oxygen-requiring gut epithelium. Although gut colonization by C. difficile is a key determinant of disease outcome, precise mechanisms of mucosal attachment and spread remain unclear. Here, using human gut epithelial monolayers co-cultured within dual environment chambers, we demonstrate that C. difficile adhesion to gut epithelial cells is accompanied by a gradual increase in bacterial numbers. Prolonged infection causes redistribution of actin and loss of epithelial integrity, accompanied by production of C. difficile spores, toxins and bacterial filaments. This system was used to examine C. difficile interactions with the commensal Bacteroides dorei, and interestingly, C. difficile growth is significantly reduced in presence of B. dorei. Subsequently, we have developed novel models containing a myofibroblast layer, in addition to the epithelium, grown on polycarbonate or 3D electrospun scaffolds. In these more complex models, C. difficile adheres more efficiently to epithelial cells, as compared to the single epithelial monolayers, leading to a quicker destruction of the epithelium. Our study describes new controlled environment human gut models that enable host-anaerobe and pathogen-commensal interaction studies in vitro.